2020
DOI: 10.1177/1751143720901690
|View full text |Cite
|
Sign up to set email alerts
|

Sugar or salt (“SOS”): A protocol for a UK multicentre randomised trial of mannitol and hypertonic saline in severe traumatic brain injury and intracranial hypertension

Abstract: Hyperosmolar solutions are widely used to treat raised intracranial pressure following severe traumatic brain injury. Although mannitol has historically been the most frequently administered, hypertonic saline solutions are increasingly being used. However, definitive evidence regarding their comparative effectiveness is lacking. The Sugar or Salt Trial is a UK randomised, allocation concealed open label multicentre pragmatic trial designed to determine the clinical and cost-effectiveness of hypertonic saline … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Despite a lack of clarity regarding the benefits of HTS in the management of acute TBI, a recent practice survey reported that most UK centers are moving to the use of HTS as first-line hyperosmolar therapy over mannitol [ 25 , 26 ]. Use of near-patient sodium monitoring (e.g., blood gas analysis) may, in part, make it easier for clinicians to use and titrate HTS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite a lack of clarity regarding the benefits of HTS in the management of acute TBI, a recent practice survey reported that most UK centers are moving to the use of HTS as first-line hyperosmolar therapy over mannitol [ 25 , 26 ]. Use of near-patient sodium monitoring (e.g., blood gas analysis) may, in part, make it easier for clinicians to use and titrate HTS.…”
Section: Discussionmentioning
confidence: 99%
“…There is a need for larger international and multicenter trials in a variety of settings to address the current lack of high-quality evidence and to determine whether there are preferred ICP-lowering therapies in specific patient populations. The ongoing Sugar or Salt phase III trial (including 25–28 ICUs across the United Kingdom) may provide further clarity on benefits or risks associated with the use of HTS in patients with acute TBI (ISRCTN16075091) [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further high-quality studies, like The Sugar or Salt Trial [25] that is planned to be finished in December 2023 funded by National Institute for Health Research in the United Kingdom, will probably bring more answers for individualized care of patients with intracranial hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Lately, the COBI RCT showed that in moderate to severe TBI patients, continuous infusion of 20% HTS compared with standard care did not improve neurological outcome at 6 months postinjury [36]. An RCT in the UK entitled “Sugar or Salt” comparing the use of bolus HTS and mannitol for the management of elevated ICP in the neurointensive care unit (NICU) setting is currently underway [37 ▪▪ ]. However, there are no RCTs targeting the prehospital and ED settings.…”
Section: Emergency Department Managementmentioning
confidence: 99%